2022
DOI: 10.1038/s41467-022-32916-7
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus agalactiae cadD alleviates metal stress and promotes intracellular survival in macrophages and ascending infection during pregnancy

Abstract: Perinatal infection with Streptococcus agalactiae, or Group B Streptococcus (GBS), is associated with preterm birth, neonatal sepsis, and stillbirth. Here, we study the interactions of GBS with macrophages, essential sentinel immune cells that defend the gravid reproductive tract. Transcriptional analyses of GBS-macrophage co-cultures reveal enhanced expression of a gene encoding a putative metal resistance determinant, cadD. Deletion of cadD reduces GBS survival in macrophages, metal efflux, and resistance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 76 publications
0
29
0
Order By: Relevance
“…In response to GBS infections, the host innate immune system deploys a repertoire of antimicrobial strategies to control bacterial burden. Our previous work has shown that the cadD locus, which encodes a putative divalent metal cation resistance determinant, is critical for GBS survival in host phagocytes . We demonstrate here that GBS virulence in the invertebrate Galleria mellonella model requires expression of the cadD locus to survive and replicate in the invertebrate host and contribute to disease progression (such as melanin induction and death) (Figure ).…”
Section: Methodsmentioning
confidence: 53%
“…In response to GBS infections, the host innate immune system deploys a repertoire of antimicrobial strategies to control bacterial burden. Our previous work has shown that the cadD locus, which encodes a putative divalent metal cation resistance determinant, is critical for GBS survival in host phagocytes . We demonstrate here that GBS virulence in the invertebrate Galleria mellonella model requires expression of the cadD locus to survive and replicate in the invertebrate host and contribute to disease progression (such as melanin induction and death) (Figure ).…”
Section: Methodsmentioning
confidence: 53%
“…While GBS has been identified as a perinatal pathogen since the 1930s, there are still major gaps in the knowledge of the pathophysiology of infection and disease outcomes by this bacterium. We have previously observed that GBS interacts with gestational tissue macrophages, and that GBS can invade the reproductive tract in a mouse model of ascending vaginal infection during pregnancy (17, 29, 47). We sought to understand the importance of individual GBS virulence factors that influence the outcome of GBS-macrophage interactions and might also have significance in clinical outcomes during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, macrophages have been implicated as a potential Trojan Horse aiding in dissemination of a variety of microbial pathogens including Candida albicans (58), Mycobacterium tuberculosis (59), Toxoplasma gondii (60), Staphylococcus aureus (61), Cryptococcus neoformans (62), and Chlamydia trachomatis (63). Depletion of host macrophages impedes Chlamydia and GBS dissemination in the reproductive tract (47, 64), demonstrating the important role that intracellular bacterial survival within macrophages plays in bacterial invasion of the reproductive tract. Our previous results indicate that GBS utilizes cadD , a metal resistance determinant, to circumnavigate metal stress within placental macrophages, and enhance bacterial ascension and invasion of the gravid reproductive tract (47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations